Evidence of quantum dot size uniformity in strain-coupled multilayered In(Ga)As/GaAs QDs grown with constant overgrowth percentage - Panda, Debiprasad; Ahmad, Aijaz; Ghadi, Hemant; Adhikary, Sourav; Tongbram, Binita; Chakrabarti, Subhananda (Journal of luminescence, 2017)
Strain coupled multi-layer quantum dot (QD) structures are limited due to their non-uniform dot size distribution, as-grown defects and dislocations. Even with these limitations, they are subject of interest because of high optical and device efficiency. In this work, we propose a modified growth strategy in which monolayer (ML) deposition of QDs is varied based on reflection high energy electron diffraction (RHEED) pattern to achieve defect free structure with uniform dot size distribution. The overgrowth percentage, i.e. monolayer deposition above critical thickness (minimum thickness required for transition from two-dimensional (2D) to three-dimensional (3D) confined structures) was kept constant in modified strategy. To verify this claim, we have compared it with conventional strain coupled multilayer structure and demonstrated improved optical performance and device characteristics. Photoluminescence spectroscopy exhibited monomodal QD distribution in strain-coupled multi-stacked heterostructure grown by the proposed strategy. Power dependent photoluminescence (PL) measurement confirms existence of single ground state peak. The proposed strategy yielded a defect free structure and better carrier capture rate compared to conventional multilayer QDs. The spectral response observed from proposed quantum dot infrared photodetector (QDIP) exhibited multiple peaks in mid-IR region (3.92µm and 4.54µm), which is one of the essential requirements for fabricating infrared detectors or focal plane arrays. Post-growth thermal annealing treatment at various temperatures (650–800°C) were performed to verify the change in activation energy, ground-state emission peak, and thermal stability. Negligible change in the ground-state PL emission peak (< 2%) and thermal activation energy (< 2%) were observed up to 750°C. The full width at half maximum (FWHM) values of the ground-state peak of the annealed samples exhibited a similar trend. High-temperature thermal stability was achieved probably due to high strain field hindering material interdiffusion and improved quantum confinement realized from uniform QD sizes. The modified growth strategy used in this paper is helpful not only for improved optical characteristics, but also for useful device performances, such as a night vision camera in defense areas, cancer detector in medical applications and fabrication of thermal imagers; focal plane arrays.